O modelo desmielinizante do brometo de etídio (be): estudos morfológicos em camundongos C57BL/6 normais e knockout para conexina 32 - Ramos, Adriano Tony (2007)
Light and ultraestructural changes of central and peripheral nervous system lesions in mice KO for connexin-32 and submitted to the ethidium bromide gliotoxic demyelinating model are described. Their KO condition was tested with PCR and a negative connexin-32 labelling was performed by immunofluorescence. The experimental animals were C57BL/6 normal mice and C57BL/6 KO for connexin-32. For all groups the animals were maintained in cages of 5 individuals within a temperature controlled room and had ration and filtered water ad libitum. A single local injection of either 0,1% ethidium bromide in normal saline (5 μl in the brainstem and 1 μl in the sciatic nerve) or normal saline was performed as described for Wistar rats. The injected mice were observed daily until euthanasia was performed at 24, 48 hours and 3, 7, 15, 21 and 30 days after injection. The mice were perfused through the heart with either neutral 10% formalin or 2,5% glutaraldehyde. Histochemical, immunohistochemical, immunofluorescence and transmission electron microscopic methods were used to analyze the development of the lesions after differentiated processing. Hematoxylin- eosine, luxol fast blue and toluidine blue methods and immunolabelling with anti-GFAP, anti-CNPase, anti-S100 protein and anti-OSP, anti Cx32 and anti Cx43 antibodies were used. Within the CNS the lesions showed an acute degenerative phase with disappearance of glial cells, and myelin sheaths were withdrawn by a scant number of macrophages. In KO mice some granulocytes were detected within the lesions in tight contact with decaying myelin sheaths. Remyelination was carried out by oligodendrocytes since no Schwann cells were seen during the regenerating process of KO mice. Occasional remyelinating Scwann cells were seen in normal mice. For the sciatic nerves, Schwann cells initially showed signs of intoxication and rejected their sheaths; after seven days, some thin newly formed myelin sheaths with uneven compaction and redundant loops (tomacula) were conspicuous. Mast cells degranulated or not were seen in all BE- induced lesions and after saline injection. It is concluded that the repair of the CNS demyelinated lesions differs from the observed in normal and immunosupressed rats because Schwann cells remyelination was absent; the absence of connexin-32 may have caused that absence. The regeneration of lost myelin sheaths within the PNS followed the pattern already reported for this model in other species. It is suggested that the absence of connexin-32 determined the different repair of the myelin sheaths within the CNS whereas for the PNS, the normal pattern of tissue response might be due to the early age of the injected mice.